2012
DOI: 10.1371/journal.pone.0041634
|View full text |Cite|
|
Sign up to set email alerts
|

Discovery of Western European R1b1a2 Y Chromosome Variants in 1000 Genomes Project Data: An Online Community Approach

Abstract: The authors have used an online community approach, and tools that were readily available via the Internet, to discover genealogically and therefore phylogenetically relevant Y-chromosome polymorphisms within core haplogroup R1b1a2-L11/S127 (rs9786076). Presented here is the analysis of 135 unrelated L11 derived samples from the 1000 Genomes Project. We were able to discover new variants and build a much more complex phylogenetic relationship for L11 sub-clades. Many of the variants were further validated usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
27
0
1

Year Published

2013
2013
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 25 publications
0
27
0
1
Order By: Relevance
“…[1][2][3][4][5] The International Society of Genetic Genealogy 10 has aggregated these variants and those discovered with previous technologies into a public resource that population surveys can leverage to further elucidate the geographic origins of and structure within haplogroups. [6][7][8][9][10][11][12][13] Y-chromosome haplogroup R (hg R) is one of 20 that comprise the standardized global phylogeny. 14 It consists of two main components: R1-M173 and R2-M479 15 (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5] The International Society of Genetic Genealogy 10 has aggregated these variants and those discovered with previous technologies into a public resource that population surveys can leverage to further elucidate the geographic origins of and structure within haplogroups. [6][7][8][9][10][11][12][13] Y-chromosome haplogroup R (hg R) is one of 20 that comprise the standardized global phylogeny. 14 It consists of two main components: R1-M173 and R2-M479 15 (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…whole-genome sequencing studies produced thousands of singlenucleotide polymorphisms (SNPs) of the MSY from a large set of males (The 1000Genomes Project Consortium 2010. A refinement of the phylogenetic relationships in a portion of the MSY tree with these SNPs has been attempted, but due to the likely abundance of false negatives and biases resulting from low-depth sequencing, not all of these SNPs could be used to confidently reconstruct and date the MSY phylogeny (Rocca et al 2012). Highdepth, whole-genome sequences have been generated and made publicly available by Complete Genomics.…”
mentioning
confidence: 99%
“…We reconstructed the phylogenetic relationships of the newly sequenced samples in the context of three other available high coverage sequences from this haplogroup using binary SNP data (Supplementary Data 1) from a total of 8.97 Mbp of sequence from the non-recombining region of nine Y-chromosomes28. For both sub-clades of R1, most Jewish sequences cluster separately from the clades that in previous studies have been shown to be common in Europe: in R1b where more than 90% of European lineages are within the L11/L52 clade29, three of the newly sequenced Jewish Y-chromosomes cluster within its copanion clade defined by the Z2105 mutation; in R1a where the majority of European individuals belong to the S198 (ref. 30) and M458 branches16, all four newly sequenced Jewish Y-chromosomes fall into the clade defined by Z94 mutation.…”
Section: Resultsmentioning
confidence: 99%